Are Working Memory Measures Free of Socioeconomic Influence? - Engel, Pascale Marguerite Josiane; Santos, Flávia Heloísa dos [UNESP]; Gathercole, Susan Elizabeth (Amer Speech-language-hearing Assoc, 2008)
Purpose: This study evaluated the impact of socioeconomic factors on children's performance on tests of working memory and vocabulary.Method: Twenty Brazilian children, aged 6 and 7 years, from low-income families, completed tests of working memory ( verbal short-term memory and verbal complex span) and vocabulary ( expressive and receptive). A further group of Brazilian children from families of higher socioeconomic status matched for age, gender, and nonverbal ability also participated in the study.Results: Children from the low socioeconomic group obtained significantly lower scores on measures of expressive and receptive vocabulary than their higher income peers but no significant group differences were found on the working memory measures.Conclusion: Measures of working memory provide assessments of cognitive abilities that appear to be impervious to substantial differences in socioeconomic background. As these measures are highly sensitive to language ability and learning in general, they appear to provide useful methods for diagnosing specific learning difficulties that are independent of environmental opportunity.
Keywords: working memory; verbal short-term memory; verbal complex span; vocabulary; socioeconomic status